Impacto da Expansão Agrícola na Amplitude Térmica Diária em Ambiente Semiárido - Correia, Magaly F.; Silva, Fabíola S.; Aragão, M. Regina Silva; Santos, Edvania P.; Moura, Magna S. B. (Ciência e Natura, 2011)
.